2021
DOI: 10.3389/fpls.2021.663750
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effect of γ-Aminobutyric Acid Against Chilling Stress During Reproductive Stage in Tomato Plants Through Modulation of Sugar Metabolism, Chloroplast Integrity, and Antioxidative Defense Systems

Abstract: Despite the role of γ-aminobutyric acid (GABA) in plant tolerance to chilling stress having been widely discussed in the seedling stage, very little information is clear regarding its implication in chilling tolerance during the reproductive stage of the plant. Here, we investigated the influence of GABA (1 and 2mM) as a foliar application on tomato plants (Solanum lycopersicum L. cv. Super Marmande) subjected to chilling stress (5°C for 6h/day) for 5 successive days during the flowering stage. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 86 publications
3
11
0
Order By: Relevance
“…For instance, GABA application induced the expression and activities of antioxidant enzymes, including CAT, APX, SOD, and phenylalanine ammonia‐lyase (PAL) during chilling stress in wheat (Malekzadeh et al, 2012). Similar results were also reported in many other plants where the application of GABA causes a reduction in chilling‐induced oxidative damage by improving the cell membrane integrity and reducing MDA and H 2 O 2 (Abd Elbar et al, 2021). Moreover, GABA‐treated wheat plants exhibited a lesser impact of chilling stress due to improved biochemical and morphological parameters (Malekzadeh et al, 2012).…”
Section: Gaba and Stress Acclimationsupporting
confidence: 85%
“…For instance, GABA application induced the expression and activities of antioxidant enzymes, including CAT, APX, SOD, and phenylalanine ammonia‐lyase (PAL) during chilling stress in wheat (Malekzadeh et al, 2012). Similar results were also reported in many other plants where the application of GABA causes a reduction in chilling‐induced oxidative damage by improving the cell membrane integrity and reducing MDA and H 2 O 2 (Abd Elbar et al, 2021). Moreover, GABA‐treated wheat plants exhibited a lesser impact of chilling stress due to improved biochemical and morphological parameters (Malekzadeh et al, 2012).…”
Section: Gaba and Stress Acclimationsupporting
confidence: 85%
“…Several lines of evidence indicated that under abiotic-stress conditions, plants trigger a number of biochemical markers which function as signaling molecules to evolve the defensive mechanisms against this stress [3,60,61]. However, the excessive accumulation of these molecules, including reactive oxygen species (ROS) such as hydroxyl radicals (OH), alkoxy radicals (RO), superoxide anion radicals (O − 2 ), singlet oxygen (O 1 2 ), and hydrogen peroxide (H 2 O 2 ) can cause serious degeneration to various plant tissues and physiological processes [10,35,[62][63][64]. Furthermore, methylglycoxal (MG) as a reactive carbonyl species has been found to be toxic at high levels leading to the restriction of plant growth and development by affecting photosynthesis, stomatal movement, cytosolic calcium, root differentiation, and seed germination [25,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…The cell-membrane stability index was estimated as described by Abd Elbar, et al [35]. Some leaf discs (8) were incubated for 24 h in 10 mL deionized water on a shaker.…”
Section: Cell Membrane Integrity and Oxidative Damagementioning
confidence: 99%
“…Lipid peroxidation was quantified by measuring the peroxidation products, thiobarbituric acid reactive substances (TBARS). TBARS was quantified by the method of Abd Elbar et al [ 34 ] by reading the developed color at 535 nm and 600 nm. Hydrogen peroxide was quantified by the colorimetric method of potassium iodide as described by Velikova et al [ 35 ].…”
Section: Methodsmentioning
confidence: 99%